Broad-Spectrum Photo-Antimicrobial Polymers Based on Cationic Polystyrene and Rose Bengal - Gavara, Raquel; de Llanos, Rosa; Pérez-Laguna, Vanesa; Arnau del Valle, Carla; Miravet, Juan F.; Rezusta, Antonio; Galindo, Francisco (Frontiers in Medicine, 2021)
New strategies to fight bacteria and fungi are necessary in view of the problem of iatrogenic and nosocomial infections combined with the growing threat of increased antimicrobial resistance. Recently, our group has prepared and described two new readily available materials based on the combination of Rose Bengal (singlet oxygen photosensitizer) and commercially available cationic polystyrene (macroporous resin Amberlite® IRA 900 or gel type resin IRA 400). These materials showed high efficacy in the antimicrobial photodynamic inactivation (aPDI) of Pseudomonas aeruginosa. Here, we present the photobactericidal effect of these polymers against an extended group of pathogens like Escherichia coli, Enterococcus faecalis, Staphylococcus aureus and the opportunistic yeast Candida albicans, using green light. The most interesting finding is that the studied materials are able to reduce the population of both Gram-positive and Gram-negative bacteria with good activity, although for C. albicans in a moderate manner. In view of the results achieved and especially considering the inexpensiveness of these two types of photoactive polymers, we believe that they could be used as the starting point for the development of coatings for self-disinfecting surfaces.